Consequences of urban pollution upon skin status. A controlled study in Shanghai area. (5th October 2015) - Lefebvre, M‐A.; Pham, D‐M.; Boussouira, B.; Qiu, H.; Ye, C.; Long, X.; Chen, R.; Gu, W.; Laurent, A.; Nguyen, Q‐L.
Synopsis: Objective: After preliminary studies aimed at measuring pertinent biochemical parameters, potentially modified in subjects exposed to bad environmental conditions, a dedicated study was performed in Shanghai city to evaluate the effect of Urban pollution upon human skin and to collect feedback from the volunteers under study. Methods: This study was performed during summer 2008 in two different districts of Shanghai, on 159 local residents: 79 subjects from Xu Jia Hui (a centre Shanghainese area), more exposed to pollution, and 80 subjects from Chong Ming, an agricultural region closely located north of Shanghai (<100 kms) and less exposed to pollution, according to official data. Biochemical parameters were measured on skin, and feedback from volunteers was collected through a graduated 'Likert scale' questionnaire under a point scale (strongly agree, agree, disagree, strongly disagree and none). Results: The study demonstrated significant differences in several biochemical parameters measured in Chong Ming area, as compared to Urban area, with an increased ratio of squalene/lipids, a lower level of lactic acid and a better cohesion of stratum corneum. Both sebum excretion rate and sebum casual levels did not differ between the two districts. The volunteer's feedback evidenced a perceived link between pollution and their skin problems. Conclusion: This study demonstrated a significant impact of the pollution upon the skin status, as illustrated by changes in superficial biochemical parameters and volunteers' perception.